Network pharmacology and molecular docking reveal the mechanisms of curcumin activity against esophageal squamous cell carcinoma - Wang, Jian; Zhang, Zhilong; Li, Qian; Hu, Zilong; Chen, Yuan; Chen, Hao; Cai, Wei; Du, Qiancheng; Zhang, Peng; Xiong, Dian; Ye, Shugao (Frontiers in Pharmacology, 2024)
Curcumin (CUR), an effective traditional Chinese medicinal extract, displays good anti-cancer activity against various cancers. Nevertheless, the impacts and fundamental mechanisms of CUR to treat esophageal squamous cell carcinoma (ESCC) yet to be comprehensively clarified. This study examined the suppressive impacts of CUR on ESCC. Methods: For a comprehensive understanding of the effect of CUR in ESCC.The CUR targets and ESCC-related genes were identified respectively, and the intersection targets between CUR and ESCC were acquired.Then, we examined the intersection targets and discovered genes that were expressed differently in ESCC. Using DAVID, enrichment analyses were conducted on the targets of CUR-ESCC. The STRING database and Cytoscape v.3.9.1 were utilized to build networks for protein-protein interaction (PPI) and drug-target-pathway. Furthermore, the interactions between CUR and its core targets were confirmed by molecular docking studies. To confirm the effects of CUR on ESCC cells, in vitro experiments were finally conducted. Results: Overall, 47 potential CUR targets for ESCC treatment were identified. The KEGG pathway enrichment analysis identified 61 signaling pathways, primarily associated with the FoxO signaling, the cell cycle, cellular senescence, the IL-17 signaling pathway which play important roles in ESCC progression. In the PPI network and the docking results identified CHEK1 and CDK6 as the core targets that positively associated with ESCC survival. CUR arrested ESCC cells at the G2/M and S phases, as shown by flow cytometry. Colony formation and CCK8 assays showed that CUR can inhibit the proliferative ability of ESCC cells. The Transwell invasion results validated that CUR can significantly inhibit the invasion rates of ESCC cells. Conclusions: Collectively, these findings indicate that CUR exhibits pharmacological effects on multiple targets and pathways in ESCC.